Zirkoniumdioxid (alveolengängige Fraktion) [MAK value documentation in German language, 2019]. Issue 3 (1st August 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated zirconium dioxide [1314‐23‐4 ]. Zirconium dioxide is a biopersistent granular dust. Therefore, the respirable fraction of zirconium dioxide dust is classified in Carcinogen Category 4 and a maximum concentration at the workplace (MAK value) of 0.3 mg/m 3 × material density is established for the respirable fraction in analogy to the other biopersistent granular dusts. Additionally, this fraction is classified in Peak Limitation Category II with an excursion factor of 8. As zirconium dioxide is not systemically distributed and accumulates only locally in the lungs, no developmental toxicity is expected to occur at the MAK value of 0.3 mg/m 3 × material density (respirable fraction). Accordingly, zirconium dioxide is classified in Pregnancy Risk Group C. Zirconium dioxide is not a sensitizer and is not taken up via the skin in toxicologically relevant amounts.